SPIRITUAL SIGNIFICANCE OF HISTORICAL MONUMENTS OF KASHKADARYA REGION - Azizova Zilola (Western European Studies, 2025)
This article analyzes the role and significance of historical and architectural monuments located in the Kashkadarya region in the spiritual education of the younger generation. Using the example of Kampirtepa, Chiroqchi Castle, Hazrati Sulaymon Mountain, Shahrisabz and other ancient monuments in the region, their cultural, educational and spiritual potential is scientifically substantiated. The author highlights the role of historical monuments in the formation of national pride, historical memory and self-awareness processes in the minds of young people, as well as the prospects for their use in educational and educational activities. The article also considers current issues related to pilgrimage tourism, preservation and restoration of historical heritage.
Keywords: Kashkadarya region; historical monuments; cultural heritage